(untitled) (Eurasian Scientific Herald, 2022)
This article also describes the exercises and assignments (new recommendations) on syntactic forms of verbs in the current native language textbooks for secondary schools of the Republic of Uzbekistan, their specifics and advantages. New recommendations have been made for syntactic formative exercises and assignments, taking into account the fact that grammar has to be taught for only one purpose - to ensure the conscious use of language